(untitled) (Papeles, 2011)
This paper presents the results of a research project the objective of which was tocharacterize the beliefs students have when interacting with multimodal texts andwhen they are involved in a foreign language learning process. The study was conductedat the Centro de lenguas of the Universidad Pedagógica Nacional, with advancedlearners of English. The literature review intended to determine the relation between education, postmodern culture, multimodal texts and students’ believes. To collectthe data, surveys, interviews and field notes were used. Findings suggest that for thestudents, multimodal texts are meaningful and motivational pedagogical tools. It wasalso found that students believe that this type of text improves their communicativeskills and helps them think critically.